Context-aware multicast routing scheme for Disruption Tolerant Networks. (27th July 2009) - Chuah, Mooi-Choo; Yang, Peng
Disruption Tolerant Networks (DTNs) are designed to enable communications in networks that experience frequent network partitions and large end-to-end delays. In this paper, we propose a Context-aware Adaptive Multicast Routing (CAMR) scheme for DTNs. Simulation results show that our CAMR scheme can achieve higher message delivery ratio with similar delay performance than two existing DTN multicast schemes, namely DTBR and OS-Multicast. We evaluate the delivery performance of CAMR in different scenarios e.g., different number of groups, different maximum node speeds. Our results indicate that CAMR scales well and provides excellent delivery performance in many different scenarios.